Pembuatan Direktori Indigenous Knowledge di Kab. Pesisir Selatan - Candra, Divo Khail; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper discusses the creation of an indigenous knowledge directory. The preparation of this directory aims to create products that can help users find relevant information about the culture of Kab. South Coast. The method used in writing this paper is: observation, interview with the local community. Based on the discussion, it was concluded that there are 10 types of culture that are no longer known to the outside or inside society. The steps in creating a directory are as follows: (a) determine the subject by searching for answers to what questions or who is expressed in sentences, and books. Usually, the subject of the book uses the word "what" question; (B) classifying / grouping the data collected according to the subject that has been determined based on the classification of the title, then the title of the developer into sections arranged according to the group; (c) prepare a directory that starts with making covers, forewords, table of contents, and directory contents and covers.Â Keyword: directory, indigeneus knowledge, pesisir selatan